1997
DOI: 10.1177/002221949703000308
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Efficacies of Neurocognitive Treatment and Homework Assistance Programs for Children with Learning Difficulties

Abstract: The purpose of the study was to analyze the relative efficacies of two treatments for children with learning difficulties. The first treatment consisted of multiple training components targeting specific cognitive and behavioral factors; the second treatment provided emotional support and supervision of school tasks. The participants were 94 Chilean schoolchildren (6 to 11 years of age). The efficacies were compared on (a) neurocognitive tests, (b) school achievement tests, and (c) behavior in school and at ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Lamminmaki et al (1997a) found an effect favoring their homework assistance control group for reading and mathematics, but there was not sufficient information to calculate effect sizes. Lamminmaki et al (1997b)-in a study that extended Lamminmaki et a!. (1997a)-found a statistically significant effect favoring intervention for reading (ES = 0.50) but not for mathematics or writing.…”
Section: Interventions For Multiple Cognitive Processesmentioning
confidence: 79%
See 1 more Smart Citation
“…Lamminmaki et al (1997a) found an effect favoring their homework assistance control group for reading and mathematics, but there was not sufficient information to calculate effect sizes. Lamminmaki et al (1997b)-in a study that extended Lamminmaki et a!. (1997a)-found a statistically significant effect favoring intervention for reading (ES = 0.50) but not for mathematics or writing.…”
Section: Interventions For Multiple Cognitive Processesmentioning
confidence: 79%
“…PREP was the focus of five studies (Boden & Kirby, 1995;Carlson & Das, 1997, Studies A and B;Das, Mishra, &: Pool, 1995;Papadopoulos, Charalambous, Kanari, & Loizou, 2004). Lamminmaki et al (1997a;1997b), Aro, Ahonen, Tolvanen, Lyytinen, and Todd de Barra (1999), and Mantzicopoulos et al (1992, Study B) also targeted a range of cognitive processes, including spatial and temporal orientation, perceptual skills, language skills, and skill integration, in addition to academic elements such as reading or numerical skills. We assigned a quality rating to this group in the average range (M= 3.83; SD = 0.83).…”
Section: Interventions For Multiple Cognitive Processesmentioning
confidence: 99%
“…Also, the simpler token reinforcement system and non-monetary rewards are likely to be more appealing to parents. While more personnel intensive studies such as the neurocognitive programme conducted by Lamminmaki et al (1997) may benefit some children, their work shows that for some, home-based instruction may bring about just as much change. We would argue, however, that unless the parents are shown how to do this, then any change brought about by specialist work in the classroom or home will not be as great as might be achieved when motivated parents provide appropriate reading strategies for their children.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently Lamminmaki, Ahonen, de Barra, Tolvanen, Michelsson and Lyttinen (1997) compared a neurocognitive treatment with a homework assistance programme. The former consisted of specialist input on perceptual, numerical and expressive language skills, provided by psychologists, speech therapists, physiotherapists and special education teachers.…”
Section: Introductionmentioning
confidence: 99%